Etnia Quinua (hoy Huamanga) - Espinoza Soriano, Waldemar (2014)
Apucuracazgo originated and evolved into what is now the province of Huamanga in Ayacucho. It takes both the Late IntermediatePeriod and the rule of Tahuantinsuyo. Its decline began with the establishment of the viceroyalty. Internally it was dividedinto Anan and Urin, with their ayllu. The Incas took a clean sweep with mitmas, especially Acos banished from the north ofCusco, as a punishment for an act committed against daring of Pachacutec. Contact with Hispanics affected its human material,owing to the spread of deadly diseases. For those who survived the colonial administration established towns with the name ofreductions. These remain Nativity Quinoa and Vinchos